Analysis of Principals’ Leadership Strategies in Improving Teacher Performance and Organizational Culture - Fathor Rakhman; Agusti Agusti; Miftahus Surur; Roni Wiranata; Wahyudi Wahyudi (Edumaspul: Jurnal Pendidikan, 2023)
The leadership of the school head is an important factor in improving teacher performance and school quality culture. This study aims to analyze the principal's leadership strategy in improving teacher performance and school quality culture. This research method uses a qualitative descriptive approach, by revealing the phenomena that occur through interviews with resource persons, observations, and documentation. The results showed that the principal had made various efforts, namely: 1) providing opportunities to attend training and professional competency development, 2) meeting the needs of learning infrastructure, 3) building good communication with all elements of the school, 4) providing feedback on the performance of each element as constructive input, 5) building effective communication and cooperation with the maximum community in increasing support and active participation in school programs. Thus, it can be concluded that the principal has implemented innovative strategies in improving teacher performance and school quality culture.